2022
DOI: 10.3390/v14102277
|View full text |Cite
|
Sign up to set email alerts
|

Cellular PSMB4 Protein Suppresses Influenza A Virus Replication through Targeting NS1 Protein

Abstract: The nonstructural protein 1 (NS1) of influenza A virus (IAV) possesses multiple functions, such as the inhibition of the host antiviral immune responses, to facilitate viral infection. To search for cellular proteins interacting with the IAV NS1 protein, the yeast two-hybrid system was adopted. Proteasome family member PSMB4 (proteasome subunit beta type 4) was found to interact with the NS1 protein in this screening experiment. The binding domains of these two proteins were also determined using this system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It is well known that NS1 (both transiently and stably expressed) enhances the translation of transient gene expression [127,128]. Recently, a report demonstrated that inducible intact NS1 or only the ED of NS1 attenuates the transcription of transient gene expression [45].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that NS1 (both transiently and stably expressed) enhances the translation of transient gene expression [127,128]. Recently, a report demonstrated that inducible intact NS1 or only the ED of NS1 attenuates the transcription of transient gene expression [45].…”
Section: Discussionmentioning
confidence: 99%
“…PSMB4 (proteasome subunit beta type 4) restricts influenza virus infection by targeting NS1 and facilitating its degradation in infected cells [ 301 ].…”
Section: Non-isgsmentioning
confidence: 99%